2022
DOI: 10.1155/2022/2657994
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Bairui Granule on Inflammatory Mediators in Induced Sputum, Leukotriene C4, and EOS in Peripheral Blood of Children with Cough Variant Asthma

Abstract: Objective. To study the effect of Hanchuan Zupa granule combined with conventional western medicine in the treatment of children with bronchial asthma. Methods. 98 cases in Fengrun District People’s Hospital of Tangshan City from June 2018 to February 2021 were selected. The control group was given oxygen therapy, antibiotics, and aerosol inhalation of quick acting β 2 receptor agonist, glucocorticoid, and other conventional western medicine treatment, while the observation group was treated with Bairui granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%